T cell receptors specific for an imatinib-induced mutation in BCR-ABL for adoptive T cell therapy - Hsu, Meng-Tung; Willimsky, Gerald; Hansmann, Leo; Blankenstein, Thomas (Frontiers in Immunology, 2025)
BCR-ABL kinase is the major oncogenic driver of chronic myeloid leukemia (CML). Tyrosine kinase inhibitors (TKIs), which are highly potent in targeting BCR-ABL, are currently used as first-line treatment. Although TKIs are effective, drug resistance caused by the emergence of drug-selected secondary mutations in BCR-ABL remains a major problem for relapse, especially in patients with compound mutations. In this study, we aimed to investigate potential neoepitopes derived from mutated BCR-ABL and to generate neoepitope-specific TCRs for adoptive T cell therapy. Two candidate peptides derived from the E255V and the T315I mutation (designated ABL-E255V and ABL-T315I) were selected for study based on their in silico predicted binding affinity to HLA-A2. By immunizing transgenic mice that express a diverse human T cell receptor (TCR) repertoire restricted to HLA-A2, we detected CD8+ T cell responses against the ABL-E255V, but not the ABL-T315I peptide. From immune responding mice, two E255V-specific TCRs were isolated. Human CD8+ T cells were engineered to express the specific TCRs for characterization, in which one TCR was identified as a therapeutic candidate due to its superior avidity and lack of detectable off-target reactivity. Importantly, we demonstrated that the ABL-E255V neoepitope was naturally processed and presented. In summary, our results demonstrate that HLA-A2+ CML cells harboring the E255V mutation can be targeted by specific TCRs, which may benefit patients who are highly resistant to available TKIs due to compound mutations.